EDITOR'S PREFACE - Lisdiyanti, Puspita (BRIN, 2008)
In this issue, 5 original research papers are presented. The fIrst paper explains the authors attempts to purify and characterize an extracellular enantio seJective lipase from Aspergillus niger, an important component for the manufacture of c1ural drugs such asibuprofen. The second papers describe the identification of a highly abundant lectin in Arabidopsis thaliana. with potential application for biopesticides against nematode. In the third paper, the authors explain an association of a polymorphism in the a-lactoglobulingene on milk yield and quality in local sheep. The fourth paper describes the authors efforts to construct a synthetic human errythropoietin (EPO) in an attempt to obtain high-yield production of the protein in yeast. And the fifth papers describes the newly develop a method to do micropropagation of buah merah (Pandanus conoideus Lam), which is a potentially important source for anticancer medication. The Editor